Implementing Access-Controlled Footpaths in Urban Roads with Consideration for Universal Design Principals - Sneha; Rajpoot A.S. (My University, 2025)
Urban road street cross-section has components such as main carriageway, service road, NMT track, Footpath, median, and multi-utility zones, each meant to provide a smooth and safe vehicular and pedestrian traffic flow. It is needless to emphasize the need to make our cities pedestrian-friendly, as it directly impacts pollution control, the health and safety of the citizens, and general well-being in all respects. This research proposes a cost-effective, easy-to-implement design solution that excludes or inhibits the movement of two-wheelers from using the footpaths meant for pedestrians and persons with disabilities (PWD), especially wheelchair users. The proposed design solution was validated through Swept Path Analysis using vehicular simulation tools, on-site experimentation, and calibration. The final design proposal uses the existing products for controlling accessibility on footpaths, like using concrete bollards. Still, the solution lies in the placement and spacing of these design elements on varying cross sections/widths of footpaths. The final solution is in the form of a series of triple bollard system (TBS) meticulously designed, calculated, calibrated, and validated drawings along with strategies to discourage the two-wheelers from using footpaths and cycle tracks meant otherwise for pedestrians/cyclists and thus creating barrier-free and user-friendly walkways across the urban landscapes, through minimum governance and on-site traffic regulation. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.